THE GENRE APPROACHES FOR TEACHERS’ STRATEGY TO DELIVER PRODUCTIVE TEACHING-LEARNING IN ENGLISH SUBJECT AT SMAN 1 KOTA LANGSA - Mauloeddin Afna afna; Cut Nisa Fadilla (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2022)
The article overviewed the teaching delivery approaches of TESOL in language teaching classroom research, which employed at SMAN 1 Kota Langsa, Aceh, Indonesia. It was advised Genre Approach (GA) for engaging discussion than a directive task, a genre which is pitching dialogues one to another between teacher and students, and specifying words of selective diction. The article projected the teaching delivery process which is engaging discussion and defines the teacher-students’ communication skill in English. It described the phenomenon by employing a semi-structured interview, which described to aim an increasing approximation to control of written and spoken texts and the activity, teacher role is facilitator and students are benefactors. The result concerned about GA and its applications profiled the series of classroom practices; preparation, screening, validation, and content review. Thus, eventually, GA also help the teacher to validate their own communication competence, their students’ development process and engagement as well.